IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Rismi; haifaturrahmah; Ineng Irma Rezkillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the Merdeka Curriculum in Indonesian language learning to improve the critical thinking skills of elementary school students. This research employed a qualitative approach with a descriptive research design. The subjects involved were a Grade V teacher and students at an elementary school. Data were collected through observation, interviews, and documentation, and analyzed through the stages of data reduction, data display, and conclusion drawing. The results show that the teacher applied project-based learning and text-based learning as part of the Merdeka Curriculum implementation. Students’ critical thinking skills improved through activities such as analyzing text content, asking questions, and expressing ideas logically. Challenges encountered by the teacher included differences in student abilities and limited learning resources. Thus, the implementation of the Merdeka Curriculum has proven effective in developing students’ critical thinking skills when supported by appropriate instructional strategies and adequate learning facilities. Keywords: Merdeka Curriculum, Indonesian Language, Critical Thinking, Elementary School